The Accusation Targeting the Narrator Khalaf al-Ahmar: A Forensic Linguistic Study - Zitouni, Nacera (Arts for Linguistic & Literary Studies, 2024)
This study seeks to apply forensic linguistics to vindicate "Khalaf al-Ahmar," a notable figure of the Basra School in literature, who faced allegations of plagiarism, fabrication, and dishonesty. It begins by defining forensic linguistics and offering a brief biography of Khalaf al-Ahmar. Subsequently, it examines both the accusations of fabrication and plagiarism, as well as the evidence supporting and refuting these claims, including relevant testimonies and news articles. Through a meticulous analysis of the initial testimonies, the study elucidates their accuracy and renders judgment on their veracity, thereby striving to rectify the injustices inflicted upon the narrator. Structurally, the research comprises an introduction, a preface, three main sections, and concluding remarks. The preface introduces forensic linguistics and delves into the linguistic realm of Khalaf Al-Ahmar. The primary sections scrutinize the accusations of plagiarism against the narrator, juxtaposing them with evidence that bolsters his credibility. The third section focuses on debunking the accusations leveled against the narrator, as disproving them substantiates the authenticity of the supportive evidence. Ultimately, the study concludes that Khalaf al-Ahmar is innocent of the alleged misconduct, attributing these accusations to a smear campaign orchestrated by his adversaries amid the rivalry between the Basra and the Kufa literary schools.